BLENDED AND ONLINE LEARNING MODELS IN FOREIGN LANGUAGE EDUCATION - Asenbaeva Xanzadaban Asenbaevna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract. The rapid development of digital technologies has strongly influenced modern education, including foreign language teaching. Today many educational institutions use blended and online learning models to improve the learning process. These approaches combine traditional teaching methods with digital tools and online resources. Blended learning integrates face-to-face instruction with online activities, while online learning is conducted completely through digital platforms. Both models provide students with more flexibility and access to a variety of learning materials. This thesis discusses the role of blended and online learning models in foreign language education and examines the ideas of several scholars who have studied technology-supported learning.